REPEATABILITY OF ANTRAL FOLLICULAR COUNT AND ITS CORRELATION WITH SUPER STIMULATION IN NILI-RAVI BUFFALOES - Q. Shahzad; A. Riaza; T. Akhter; A. Sattara; J. Nazirb; A. A. K. Niazi; A. Azamc; A. U. Husnac (Journal of Animal and Plant Sciences, 2014)
Small ovarian size and low number of follicles are major causes of low reproductive potential in buffalo (Bubalus bubalis). There is no tool through which reproductive performance of buffalo can be phenotyped. Therefore, aim of the present study was to develop a method on the basis of which reproductive performance of buffaloes can be phenotypically assessed. For this purpose two experiments were designed. In first experiment, ten Nili-Ravi buffalo heifers were used in the study to measure repeatability of follicular count. Each heifer was scanned on alternate day, from day 1 to day 9 of the successive estrous cycle. Antral follicles and repeatability was assessed in different follicular waves. In 2nd experiment, 4 lactating buffaloes were selected to count antral follicles from day 1 to day 10 of the estrous cycle and super-stimulated by using FSH hormone. Follicular count after FSH injection was examined by ultrasound. Follicular count is highly repeatable in different follicular waves within (r = 0.83) and between (r = 0.85) different estrous cycles. Follicular count and super stimulatory response are positively correlated (r = 0.95). In conclusion, animals with high antral follicular count can be selected for super stimulation and embryo transfer to get optimum response.
Keywords: Antral follicular count; Super-stimulation; Repeatability; Buffalo